Exercise increases serum fibroblast growth factor 21 (FGF21) levels. - Daniel Cuevas-Ramos; Paloma Almeda-Valdés; Clara Elena Meza-Arana; Griselda Brito-Córdova; Francisco J Gómez-Pérez; Roopa Mehta; Jorge Oseguera-Moguel; Carlos A Aguilar-Salinas (PLoS ONE, 2012)
Fibroblast growth factor 21 (FGF21) increases glucose uptake. It is unknown if FGF21 serum levels are affected by exercise.This was a comparative longitudinal study. Anthropometric and biochemical evaluation were carried out before and after a bout of exercise and repeated after two weeks of daily supervised exercise. The study sample was composed of 60 sedentary young healthy women. The mean age was 24±3.7 years old, and the mean BMI was 21.4±7.0 kg/m². The anthropometric characteristics did not change after two weeks of exercise. FGF21 levels significantly increased after two weeks of exercise (276.8 ng/l (142.8-568.6) vs. (460.8 (298.2-742.1), p<0.0001)). The delta (final-basal) log of serum FGF21, adjusted for BMI, showed a significant positive correlation with basal glucose (r = 0.23, p = 0.04), mean maximal heart rate (MHR) (r = 0.54, p<0.0001), mean METs (r = 0.40, p = 0.002), delta plasma epinephrine (r = 0.53, p<0.0001) and delta plasma FFAs (r = 0.35, p = 0.006). A stepwise linear regression model showed that glucose, MHR, METs, FFAs, and epinephrine, were factors independently associated with the increment in FGF21 after the exercise program (F = 4.32; r² = 0.64, p<0.0001).Serum FGF21 levels significantly increased after two weeks of physical activity. This increment correlated positively with clinical parameters related to the adrenergic and lipolytic response to exercise.ClinicalTrials.gov NCT01512368.